VARIATION OF HARMONICS EMISSION FROM MODERN LAMPS IN A POWER SUPPLY NETWORK - RÓBERT ISTÓK (Journal of Engineering Studies and Research)
The objective of this paper is to prove the relationship between the Total Harmonics Disturbance emission of lamps network and the number of lamps. In the lighting field the LED lighting emission diode is the absolutely winner. The low power consumption and the characteristics of LED made it ideally for most of indoor and outdoor applications. The dimmability of the LEDs which is between 0% and 100% made it ideally for intelligent lighting applications. This large dimmability range could be obtained only with incandescent and halogen bulbs, compare to CFL compact fluorescent lamps where the maximum dimmability is around of 60%. One of the prices of this positive characteristics of modern lamps, is the electromagnetic compatibility EMC. It is well known that the modern lamps have a common part, and this is the electronic ballast. And as all electronics circuits, the electronic ballasts are an important source of EMC noise emission. The noise emission of electronic ballast is mainly conducted emission type. Start from construction of electronic ballast which contains an AC/DC converter and a buffer capacitor the emission of half harmonics is presented too. The emission of half harmonics is proportionally with the cost of lamps, because the cost of lamps depends by the methods used for noise emission rejection too. Typically the cheaper lamps have a higher noise emission than the expensive lamps. Known of noise emission lamps separately is not enough for characterization of low noise emission from lighting network. The low frequency noise emission of a lighting network is lower than in case of a single lamp. The variation of temperature determines a variation of low frequency noise emission too.